A Class I HDAC Inhibitor BG45 Alleviates Cognitive Impairment through the CaMKII/ITPKA/Ca2+ Signaling Pathway - Jingyun Liu; Chenghong Zhang; Jiale Wang; Yufei Huang; Di Shen; Yingqiu Hu; Haiying Chu; Xuebin Yu; Liyuan Zhang; Haiying Ma (MDPI AG, 2022)
Alzheimer's disease (AD) seriously endangers the health and life of elderly individuals worldwide. However, despite all scientific efforts, at the moment there are no effective clinical treatment options for AD. In this work, the effect of the class I histone deacetylase inhibitor (HDACI) BG45 on synapse-related proteins was investigated in primary neurons from APP/PS1 transgenic mice. The results showed that BG45 can upregulate the expression of synaptotagmin-1 (SYT-1) and neurofilament light chain (NF-L) in primary neurons. In vivo, the APPswe/PS1dE9 (APP/PS1) transgenic mice were treated with BG45 (30 mg/kg) daily for 12 days. Behavioral testing of BG45-treated APP/PS1 mice showed improvements in learning and memory. BG45 can alleviate damage to the dendritic spine and reduce the deposition of Aβ. Similar to the in vitro results, synapse-related proteins in the prefrontal cortex were increased after BG45 treatment. Proteomic analysis results highlighted the differences in the biological processes of energy metabolism and calmodulin regulation in APP/PS1 mice with or without BG45 treatment. Further verification demonstrated that the effect of BG45 on synapses and learning and memory may involve the CaMKII/ITPKA/Ca2+ pathway. These results suggest that class I HDACI BG45 might be a promising drug for the early clinical treatment of AD.